Evidence-based Assessment and Intervention into Adolescent Oral Health Care Access - Faris Rowais Almasabi; Aziz zead Alkathiry; Najoud Saleh alhawiti; Kholod Abdullah Madini; Rami Amin Alsous; Hussain Ali aljuaid; Seham ageel Al-Anazi; Ebtisam mesfer almalki; Yousef Obaid Mana Aldarami; Arwa Abdulrahman Abdulmohsen AlAbdulkader (International Journal of Medical Toxicology and Legal Medicine, 2024)
Adolescent oral health is animportant piece of one’s body, playing heavily into the overall quality of life through vital activities such as eating, conversing, and socializing.Adolescent oral health is an important piece of one’s body, playing heavily into the overall quality of life through vital activities such as eating, conversing, and socializing. This review investigates the application of dental care among adolescents, recognizing key factors that impact access and discrepancies in oral health outcomes. Because adolescence is an important time for establishing lifelong oral health behaviors, many adolescents face barriers to dental care due to socioeconomic status, cultural influences, psychological factors, and geographical constraints.As such, there is a higher burden of oral diseases —dental caries (tooth decay), periodontal disease (gum disease or severe gum inflammation), malocclusion, and oral cancer—among these less privileged groups. Public health interventions, such as school-based programs, community water fluoridation, and policy changes removed disparities in oral health outcomes.Today, recent advancements in dental care, such as the emergence of Teledentistry, minimally invasive dentistry strategy, mobile health (mHealth) applications, and personalized care, offer hopefulapproaches for addressing these challenges. Beginning to blend oral health into primary care and using behavioral interventions that include motivational interviewing, are necessarycomponents of advancing the positives for improving oral health behaviors and reducing barriers to care. Conclusions This review identified the necessity of targeted public health approaches, technology-based solutions, and culturally sensitive service provision to address current disparities in dental service access for adolescents and includes aspects relevant to reducing oral disease burden.